Quantification of DNA binding, uptake, transmission and expression in bovine sperm mediated gene transfer by RT-PCR: Effect of transfection reagent and DNA architecture - Michael Hoelker (2018)
In this study, we compared the transfection effectiveness of liposomes with the new transfection reagent FuGene 6 in bovine sperm mediated gene transfer (SMGT). Furthermore, we examined whether plasmid architecture affects overall efficiency by comparing two plasmids, one of them bearing an additional murine nontranscribed spacer (nts) insert (CMV-INF-τ-IRES-EGFP versus CMV-INF-τ-IRES-EGFP-nts). To accomplish that, we quantified plasmid binding and uptake to spermatozoon and transfer and expression of foreign DNA into embryos by real time PCR. More plasmids bound to spermatozoa when treated with FuGene 6 than with liposome treatment (p < 0.05) reaching highest counts in plasmids bearing the nts sequence (p < 0.05). Mean number of plasmids taken up was significantly (p < 0.05) affected by transfection strategy (1-3 versus 15-81 versus 120-162) with plasmids bearing the nts sequence being 2-8 fold more effective (p < 0.05). Culture of SMGT derived embryos up to day 9 did not result in any difference in terms of cleavage rate (64.2-84.2%) and development to blastocyst stage (18.8-26.3%) between different groups. Insert of the nts fragment significantly (p < 0.05) affected mean number of transmitted plasmids to 4-cell stage embryos (44 versus 7) and relative INF-τ mRNA expression level in day 9 blastocysts (7-8 fold). However, only six blastocysts (3.6%) exhibited green fluorescence indicating low EGFP protein production. In conclusion, we were able to show effectiveness of sperm mediated gene transfer is significantly affected by choice of transfection reagent and by plasmid architecture. © 2007 Elsevier Inc. All rights reserved.